5 Characterisation of the structural and electrical impact of an atrial septal defect: patterns of atrial ectopy on continuous holter monitoring. (October 2018) - O'Neill, L; Williams, S; Whitaker, J; Sim, I; Mukherjee, R; Harrison, J; Julia, J; Sugihara, C; Niederer, S; Wright, M; Frigiola, A; O'Neill, M
Abstract : Background: Atrial fibrillation (AF) is common in atrial septal defect patients (ASD) but little is known about the triggers for these arrhythmias. Hypothesis: Since right atrial dilatation is well described in ASD patients we hypothesised that atrial ectopy in ASD patients would be predominantly right-sided in origin. Objective: 1. To determine the origin of ectopy recorded on continuous Holter monitoring in ASD patients compared to atrial fibrillation (AF) patients with structurally normal hearts. 2. To identify echo and CMR parameters associated with ectopy in an ASD population. Methods: The origin of atrial ectopic beats was determined by measuring P wave amplitude in three Holter leads and calculating the axis for each ectopic beat. Invasive validation was performed by calculating P wave axes as recorded on Holter monitoring during intracardiac pacing from multiple right and left atrial sites in patients with structurally normal hearts undergoing catheter ablation. Haemodynamic parameters from echo/MRI and invasive catherisation, when available, were recorded in the ASD patients and correlated with arrhythmia occurrence and atrial ectopic burden (figure 1). Results: Analysis of Holter monitoring P wave vectors during intra-cardiac pacing across 35 sites demonstrated that a vector between 90° and 270° had a 90.5% sensitivity and 85.7% specificity for predicting an ectopic beat of left sided (vs right sided) origin. Therefore, ectopic P waves with a vector angle of 90–270° were considered left sided while those with an angle of 0–90° or 270–360° were considered right sided. 189 ectopic beats were analysed in 33 ASD patients (14 male, mean age 50.1±16.9 years). 149 ectopic beats were analysed in 37 control patients (21 male, mean age 61.6±10.5) (table 1). Right sided ectopy accounted for 71.4% of all ectopic beats studied in the ASD population and was significantly more prevalent in the ASD population than in the control population (p=0.003). Qp:Qs was significantly associated with the presence of documented atrial arrhythmias in the ASD population (p=0.04). Overall ectopic burden over 24 hours correlated significantly with LA size by 2D echo (R=0.464, p=0.008). Conclusion: Right sided ectopy is more prevalent in ASD patients compared to non-ACHD AF patients. This data suggests that arrhythmia triggers are more likely to be right sided in origin compared to NCHD AA patients This observation may have implications for arrhythmia intervention strategies in this cohort. Further investigation is required to determine the role of right-sided ablation as an adjunct to pulmonary vein isolation in ASD patients with AF.